Analisis Kontribusi, Efektivitas, dan Potensi Penerimaan Pajak Reklame terhadap Pendapatan Asli Daerah Kota Banjarmasin - Rusdiyana, Nisa; Saleh, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research  was conducted to determine the Contribution, Effectiveness, and Potential of Receipt of Advertisement Tax to Regional Original Income in Banjarmasin. The data used in the form of secondary and primary data with research samples selected by stratified random sampling as many as 5 streets location  from 29 streets location in Banjarmasin. This data analysis technique using descriptive analysis with the quantitative method. The results of this study indicate that the Contribution of receipt of Receipt of Advertisement Tax to Regional Original Income in Banjarmasin during the 2017-2021 budget year was still very poor. Effectiveness of Advertisement Tax in Banjarmasin tends to fluctuate, it happens in 2017-2021. Potential of Receipt Advertisement Tax in Banjarmasin on Regional Original Income in Banjarmasin is Rp 4.868.586.958,42,-  or 63,39%.